1986
DOI: 10.1515/znc-1986-1-232
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies on the Biosynthesis of Granaticin

Abstract: Experiments with cerulenin-inhibited cultures of 5. violaceoruber showed conversion of dihydrogranaticin (II) into granaticin (I), but not vice versa, confirming an earlier conclusion that II is the biosynthetic precursor of I. Feeding of CH313C18O2Na followed by 13C-NMR analysis of the product by the 18O shift method indicated the expected incorporation of 18O at carbons 1,11 and 13 of I and showed that the oxygen of the pyran ring originates from C-3 and not from C-15. Analysis of I biosynthesized from 13C2H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
1

Year Published

1986
1986
2002
2002

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
1
6
1
Order By: Relevance
“…Such an observation is inconsistent with the use of either FabH or FadA to initiate TCM C biosynthesis directly from acetyl-CoA (Figure 2). A similar lack of intact incorporation of deuterium label from [2-13 C, 2 H 3 ]acetate has been reported for the starter unit of granaticin (22). This observation led to a suggestion of malonyl-CoA as a starter unit, which is decarboxylated by the "enzyme matrix".…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Such an observation is inconsistent with the use of either FabH or FadA to initiate TCM C biosynthesis directly from acetyl-CoA (Figure 2). A similar lack of intact incorporation of deuterium label from [2-13 C, 2 H 3 ]acetate has been reported for the starter unit of granaticin (22). This observation led to a suggestion of malonyl-CoA as a starter unit, which is decarboxylated by the "enzyme matrix".…”
Section: Resultssupporting
confidence: 66%
“…This observation led to a suggestion of malonyl-CoA as a starter unit, which is decarboxylated by the "enzyme matrix". In the granatacin study NMR analysis of the methyl group derived from the starter unit demonstrated no evidence of 13 C 2 H 3 but some level of 13 C 2 H 2 and 13 C 2 H species (22). In our study on TCM C we did not see any evidence for these species.…”
Section: Resultscontrasting
confidence: 65%
“…Snipes et al 1979). Feeding experiments have established that granaticin is synthesized from eight molecules of acetate and one molecule of glucose (Snipes et al 1979;He et al 1986). 1).…”
Section: Introductionmentioning
confidence: 99%
“…nidulans group) (9). Another group of compounds comprises the benzoisochromane quinones, such as actinorhodin (10) and granaticin (1 l), whose relevant structural moieties (12) have been shown to be of polyketide origin by extensive biosynthetic studies (10,11). The latter compounds, however, are metabolites of actinomycetes, that is, prokaryotic organisms which may not be encompassed by the rule.…”
mentioning
confidence: 99%